Superior physiological adaptations after a microcycle of short intervals versus long Intervals in cyclists - Rønnestad, B. R.; Øfsteng, S. J.; Zambolin, F.; Raastad, T.; Hammarström, D. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare the effects of a 1-week high-intensity aerobic-training shock microcycle composed of either 5 short-interval sessions (SI; n = 9, 5 series with 12 × 30-s work intervals interspersed with 15-s recovery and 3-min recovery between series) or 5 long-interval sessions (LI; n = 8, 6 series of 5-min work intervals with 2.5-min recovery between series) on indicators of endurance performance in well-trained cyclists.